Exploring potential of longan - Kumar, Rajesh; Kumar, Vinod (Indian Horticulture, 2019)
Longan (Dimocarpous longan), is a subtropical tree, producing edible fruits. It is one of the better known commercially cultivated crop member of the soapberry family, to which litchi belongs. It is native to southern Asia. Scientists of National Research Centre on Litchi in Bihar are doing evaluation and propagation studies from 2004 under its R&D activities to boost longan cultivation in India. The resultant efforts indicated that after litchi made a mark and is now treated as pride of Bihar, its cousin longan can also make a sweet presence as potential crop in Bihar. It has been found suitable for growth in state’s northern belt.